Gambaran Kadar Glukosa Darah pada Pengguna Kontrasepsi Suntik di Wilayah Kerja Puskesmas Telaga Dewa - Margareta Febriana Simanihuruk; Welkriana, Putri Widelia; Halimah (Jurnal Sanitasi Profesional Indonesia, 2025)
The surge of estrogen and progesterone hormones from injectable contraceptives increases blood glucose levels by suppressing the insulin response to elevated glucose levels, thereby causing contraceptive effects to counteract insulin function. This study aims to determine fasting blood glucose levels among injectable contraceptive users in the working area of the Telaga Dewa Health Centre, Bengkulu City. This study used a descriptive research design. Fasting blood glucose levels were measured using a spectrophotometer with venous blood samples. The population consisted of 36 injectable contraceptive users within the working area of the Telaga Dewa Health Centre, Bengkulu City. Data were collected through direct observation using an accidental sampling technique. Data analysis was performed using univariate methods. The study involved 36 respondents. The results showed that 41.7% of injectable contraceptive users had abnormal fasting blood glucose levels, 27.8% were in the prediabetic range, and 30.5% had normal levels. Most users (36.1%) were aged 20–30 years, followed by 30.3% aged 41–50 years, 27.8% aged 31–40 years, and 2.8% aged ≥ 50 years. In terms of duration of use, 55.6% had been using injectable contraceptives for 1–4 years, 44.4% for ≥ 5 years, and none for ≤ 1 year (0%). A significant portion (41.7%) of injectable contraceptive users had abnormal fasting blood glucose levels. This study is expected to contribute to greater awareness of the importance of maintaining a healthy lifestyle among injectable contraceptive users.